The Effectiveness of Antibiofilm Synergy of Parijoto Leaf Extract (Medinilla speciosa) and Gentamicin on Methicillin-Resistant Staphylococcus aureus (MRSA) from Diabetic Ulcers - Arina Lis Sa'adah; Fariza Yulia Kartika Sari; Bintari Tri Sukoharjanti; Sri Darmawati (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Diabetic foot ulcers (DFU) are chronic complications of diabetes that are generally accompanied by bacterial infections. Methicillin-Resistant Staphylococcus aureus (MRSA) is one of the most dominant pathogenic bacteria isolated from DFU wounds. The significant number of MRSA bacteria and the formation of bacterial biofilms result in prolonged wound treatment and high amputation rates. Several medicinal plants in the Muria Mountains have the potential to be alternative antibiofilms supporting gentamicin antibiotic treatment, one of which is the parijoto plant (Medinilla speciosa). This study aims to evaluate the effectiveness of the combination of parijoto leaf extract with gentamicin in inhibiting the growth of MRSA biofilms isolated from DFU. Parijoto leaves were extracted using the UAE (Ultrasound-Assisted Extraction) technique, followed by phytochemical tests and antibiofilm inhibition tests using the microdilution method. The results of phytochemical identification showed that there were saponin, flavonoid, tannin, alkaloid, quinone, and phenol compounds. The combination of gentamicin and parijoto leaf extract with several variations obtained the highest percentage of biofilm inhibition, namely 95%. The IC50 value in the antibiofilm inhibition test of the combination of parijoto leaf extract and gentamicin was 6.90 μg/mL. The chemical bioactive content in parijoto leaf extract can synergize as a supporting treatment with gentamicin to accelerate the treatment of diabetic ulcer wound infections. Further research needs to be carried out to explore and further study to determine the QS (Quorum Sensing) mechanism against MRSA (Methicillin-Resistant Staphylococcus aureus) bacteria by bioactive compounds in parijoto leaf extract and invivo test.